Takbir Keliling Sebagai Bentuk Komunikasi Dakwah: Analisis Behaviorisme Stimulus–Respon dalam Tradisi Idulfitri Desa Lempuyang - Siti Mu'awanah; Saepullah; Aufa Hanun Nadia (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2026)
This study aims to examine the takbir keliling tradition in Lempuyang Village, Demak, as a form of da’wah communication practice through the lens of behaviorist communication theory, which emphasizes the stimulus–response relationship. Employing a descriptive qualitative approach with a case study design, the research engaged community members actively involved in takbir keliling selected via purposive and snowball sampling techniques. Data were gathered through in-depth interviews, participant observation, and documentation, and subsequently subjected to thematic analysis by identifying and categorizing stimulus and response patterns within the behaviorist framework.The findings indicate that da’wah communication stimuli within the takbir keliling tradition encompass the establishment of organizing committees, dissemination of announcements and invitations, intensive frequency of gatherings, community-based fundraising, and the deployment of religious symbols alongside technological media such as LED lighting and sound systems. Community responses manifest in enhanced comprehension of the religious significance of takbir keliling, the emergence of affective responses including happiness and pride, active involvement in preparatory and executional activities, and strengthened interpersonal and communal bonds. The stimulus–response interaction thereby contributes to the reinforcement of religious practices and social cohesion, while simultaneously affirming the explanatory utility of behaviorist theory in analyzing tradition-based da’wah practices. This study offers a scholarly contribution to the fields of communication and da’wah studies by proposing an empirical model that illustrates how religious cultural traditions can function as effective da’wah media through the systematic orchestration of stimuli and corresponding responses.